Information in Crisis: Analysing the Future Roles of Public Libraries during and post-COVID-19. Issue 4 (1st October 2020) - Smith, Jade
ABSTRACT: The COVID-19 pandemic has caused disruption to public library services and systems in Australia and around the world. The social, cultural, economic and commercial impacts of the pandemic will require creativity and adaptability at both an individual and organisational level, with 'business as usual' no longer an option for many. This paper discusses innovations that have been introduced to maintain relevance, connect with vulnerable communities beyond the library branch, and encourage online engagement while patrons are in extended lockdowns or otherwise COVID-affected and isolated. It proposes that issues that may arise after the initial pandemic response and ways in which they may be addressed by Australian public libraries, for example ensuring safety and efficiency of continued public library services, monitoring research into the infection risk and cleanliness of surfaces as relating to library materials, following changing government guidelines and regulations, and potentially agitating for further funding to meet these changing needs. The challenges and opportunities are varied during these uncertain times, but public libraries retain their core mission to support digital literacies and act as gateways to information. Research and innovation lead by library staff can and should ensure that this continues into the future.